Implementasi kebijakan pengentasan kemiskinan di Kabupaten Kendal - Ariningsih, Siti (Institute for Advanced Science Social, and Sustainable Future, 2024)
The national goals of the Unitary State of the Republic of Indonesia which have been initiated by the founders of the country as stated in the Preamble of the 1945 Constitution in the fourth paragraph are: 1) to protect the entire Indonesian nation and all of Indonesia's blood spilled 2). Promote general welfare 3). educating the nation's life and 4). Participate in carrying out world order based on freedom, eternal peace and social justice. To achieve this goal, especially the government's obligation to serve the poor, the government regulates in Law Number 11 of 2009 concerning Social Welfare. In particular, Articles 19 and 20 specifically discuss poverty. Poverty is very important and requires serious attention by the government, poverty alleviation programs are a priority program in development. The success and effectiveness of poverty alleviation programs is highly dependent on the policies set by the central government and regional governments and involves many government institutions in its implementation